Teaching the caregiver the art of caring: an educational care program with multiple trauma patient caregivers - Rangel Flores, Yésica Yolanda; Hernández Flores, María Magdalena; García Rangel, Minerva (Investigación y Educación en Enfermería, 2010)
<!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- /* Font Definitions */ @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-520092929 1073786111 9 0 415 0;} @font-face {font-family:NewsGothicBT-Bold; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 0 0 0 1 0;} @font-face {font-family:NewsGothicBT-Roman; panose-1:0 0 0 0 0 0 0 0 0 0; mso-font-charset:0; mso-generic-font-family:auto; mso-font-format:other; mso-font-pitch:auto; mso-font-signature:3 0 0 0 1 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} .MsoPapDefault {mso-style-type:export-only; margin-bottom:10.0pt; line-height:115%;} @page WordSection1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.WordSection1 {page:WordSection1;} --><!-- [if gte mso 10]> <![endif]--> Objective: to evaluate the effectiveness of an educational intervention program framed in self-care deficit theory addressed to multiple trauma patients´ caregivers at a hospital in san luis potosí in Mexico. Methodology: interventional longitudinal comparative study; Probabilistic systematic sampling was done with randomized assignation of the intervention. The study variables were: Caregivers level of knowledge and the multiple trauma patient evolution. An educational intervention program was applied to the caregivers throughout five sessions; the control group received conventional education by the health staff during their multiple trauma patient hospitalization. Knowledge level measurements were applied before and after the intervention to both groups, as well as a complete nursing assessment pre and post intervention aiming to identify disuse syndrome characteristic complications. The data was analyzed using descriptive statistics and inferential measures. Results: There is statistical evidence of the educational program effectiveness. As it not only improved the caregivers level of knowledge but the multiple trauma patients of the group had a lower incidence of complications secondary to prolonged immobility. Conclusion: the intervention program resulted effective favoring the caregiver’s level of knowledge as well as the evolution and prevention of complications in the multiple trauma patient.